Guzi yu jian Douzi - Tang Tang 1977- (Cai wu ya zhong wen yuan chuang xi lie, 2013)
Millet is adopted, and this causes him to be a little melancholy until he meets Bean. Bean is actually an alien that has lost his wings, and Millet hides him under his bed, standing by his promise to protect Bean at all costs. In the end, Bean regrows his wings and returns to his mother’s side, and Millet comes to understand that those around him are his real, closest family.